Farm mechanization in Indian agriculture with focus on tractors - Ashok Gulati; Ritika Juneja (University of Bonn, Center for Development Research (ZEF), 2020)
Indian agriculture is dominated by smallholders. With an average holding size of just 1.08 hectares (ha) (in 2015-16), and 86 percent of holdings being of less than 2 ha in size, Indian agriculture transformed the country from functioning 'ship-to-mouth' during the mid-1960s to being a net exporter of agri-produce today. This would not have been possible without the onset of the Green Revolution post-1965, which resulted in increased foodgrain production and productivity. Among various inputs such as seeds, irrigation and fertilizers, the productivity of farms also depends greatly on the availability and judicious use of farm power by the farmers. Between the mid-20th century and 2013-14, India witnessed a tremendous shift away from traditional agriculture processes to mechanized processes. Today, 88 percent of the total farm power comes from tractors, diesel engine pump-sets, electric pump-sets and power tillers (2013-14). Additionally, India has emerged as the largest manufacturer of tractors in the world, followed by the USA and China. But how has farm mechanization, especially the use of tractors, evolved in India over time? What were the key drivers of the demand for tractors? And how efficiently are the tractors being used in terms of usage by number of hours/year? Given the high cost of tractors, it is also interesting to see how far they have penetrated the small and marginal holdings, i.e., the issues of inclusiveness, financial viability and sustainability. These are some of the key questions that are addressed in this study. [...]
Keywords: Q1; Q12; Q15; O31; 330; Farm Mechanization; Tractors; Custom Hiring Centres; Uberization